Milestones and Impact Factors - Grandjean Philippe; Ozonoff David M (BMC, 2010)
Abstract Environmental Health has just received its first Impact Factor by Thomson ISI. At a level of 2.48, this achievement is quite satisfactory and places Environmental Health in the top 25% of environmental science journals. When the journal was launched in 2002, it was still unclear whether the Open Access publishing model could be made into a viable commercial enterprise within the biomedical field. During the past eight years, Open Access journals have become widely available, although still covering only about 15% of journal titles. Major funding agencies and institutions, including prominent US universities, now require that researchers publish in Open Access journals. Because of the profound role of scientific journals for the sharing of results and communication between researchers, the advent of Open Access may be of as much significance as the transition from handwriting to printing via moveable type. As Environmental Health is an electronic Open Access journal, the numbers of downloads at the journal website can be retrieved. The top-20 list of articles most frequently accessed shows that all of them have been downloaded over 10,000 times. Back in 2002, the first article published was accessed only 49 times during the following month. A year later, the server had over 1,000 downloads per month, and now the total number of monthly downloads approaches 50,000. These statistics complement the Impact Factor and confirm the viability of Open Access in our field of research. The advent of digital media and its decentralized mode of distribution - the internet - have dramatically changed the control and financing of scientific information dissemination, while facilitating peer review, accelerating editorial handling, and supporting much needed transparency. Both the meaning and means of "having an impact" are therefore changing, as will the degree and way in which scientific journals remain "factors" in that impact.